2012
DOI: 10.1165/rcmb.2011-0309oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alveolar Epithelial Na+ Channels by ERK1/2 in Chlorine-Breathing Mice

Abstract: The mechanisms by which the exposure of mice to Cl 2 decreases vectorial Na 1 transport and fluid clearance across their distal lung spaces have not been elucidated. We examined the biophysical, biochemical, and physiological changes of rodent lung epithelial Na 1 channels (ENaCs) after exposure to Cl 2 , and identified the mechanisms involved. We measured amiloride-sensitive short-circuit currents (I amil ) across isolated alveolar Type II (ATII) cell monolayers and ENaC single-channel properties by patching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…In both cases there is increased generation of reactive intermediates, which lasts after the cessation of exposure. For example, we have previously shown the presence of reactive intermediates in lung epithelial cells exposed to Cl 2 and returned to room air using electron spin resonance and redox sensitive dyes (42). Increased levels of reactive intermediates were also documented in the lungs of mice and rats exposed to Cl 2 and returned to room air by measuring levels of isoprostanes (75) and products of lipid peroxidation (77).…”
Section: Discussionmentioning
confidence: 97%
“…In both cases there is increased generation of reactive intermediates, which lasts after the cessation of exposure. For example, we have previously shown the presence of reactive intermediates in lung epithelial cells exposed to Cl 2 and returned to room air using electron spin resonance and redox sensitive dyes (42). Increased levels of reactive intermediates were also documented in the lungs of mice and rats exposed to Cl 2 and returned to room air by measuring levels of isoprostanes (75) and products of lipid peroxidation (77).…”
Section: Discussionmentioning
confidence: 97%
“…The picture is further complicated by the presence of more than one type of amiloride-sensitive channel in alveolar epithelium. A recent study by Lazrak et al (239) showed that two amiloride-sensitive channels, with single-channel conductances of 4.5 pS and 18 pS, could be recorded from ATI And ATII cells in lung slices from airbreathing mice. The 4.5 pS channel was highly selective for sodium and most likely corresponds to ␣␤␥ENaC, while the larger channel was less sodium selective and its molecular identity is currently unknown.…”
Section: Enac In Non-cf-related Lung Diseasementioning
confidence: 99%
“…Exposures during the accidental release of Cl 2 have been modeled based on the Graniteville accident and have shown that Cl 2 levels during a 30-min exposure period were 6,868, 837, and 89 ppm at 0.2, 0.5, and 1 km downwind from the epicenter of the accident (5). Previous studies from our group and those of others have shown that mice exposed to 400 ppm Cl 2 for 30 min and returned to room air develop acute hypoxia, lung inflammation accompanied by perturbation of the integrity of the alveolar epithelial barrier, and significant lung oxidative stress (30,33,48,57,58). Moreover, there were also alterations in respiratory mechanics (34,45), compromised immune response to fungi (16), and impaired locomotion (13).…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, there is a large body of experimental evidence indicating that thrombin increases lung endothelial permeability via a protease-activated receptor-dependent mechanism (28) and alveolar epithelial permeability via an ␣ v ␤ 6 integrin-and TGF-␤-dependent mechanism (25) and compromises vectorial sodium transport via activation of PKC (50). In addition, it may act synergistically with reactive intermediates that are known to be generated both during and after exposure to Cl 2 both in vitro and in vivo (30,57), to activate the small GTPase RhoA and suppress Rac1, which also contribute to increased alveolar permeability and pulmonary edema (3,15). Heparin may abate these processes by preventing the continued formation of thrombin or by acting as an anti-inflammatory, which prevents epithelial damage and exposure of pulmonary thrombin to the systemic coagulation system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation